Non-Human World in Ernest Hemmingway’s The Old Man and the Sea - Bhattarai, Kedar (Journal of Tikapur Multiple Campus, 2023)
This study explores human attitude towards non-human world in Ernest Hemmingway’s The Old Manand the Sea. The narrative in Hemmingway’s masterpiece The Old Man and the Sea integrates human and non-human world. However, in this paper, I assume that Hemmingway displays contradictory attitude towards non-human world. The study uses post humanism as a theoretical lens. It employs the critical insights forwarded by Deleuze and Guattari, Val Plumwood, and Donna Haraway as the theoretical parameters to analyze the selected text. The study involves the exploration of the nature of the relations between the entities human and animal. Besides, the study seeks relationality, the interspecies connection, along with the recognition of embodiment, instinct and finitude as the shared ontological grounds in the selected narrative. The study suggests that Hemmingway offers both anthropocentric and biotic attitude towards non-human world.